Nurses' role play in perspective from prenatal and natural childbirth humanization program: a systematic review study - Avanci, Barbara Soares; Cortez, Elaine Antunes; Barbosa, Fernanda Salustiano; André, Keila Magalhães (Revista de Enfermagem UFPE on line, 2009)
Objectives: to identify the knowledge and expectations of women in the choice of natural childbirth, discuss the program of humanization of prenatal and birth and the role of the nurse in encouraging the humane and natural childbirth. Methods: it’s a literature search, type descriptive-exploratory, with a qualitative approach. Was carried out a search in the databases using the descriptors nursing, labor and delivery man. Refine the data by reading pre-textual, selective and interpretative. Results: emerged the categories: knowledge and expectations of women in the choice of natural childbirth; program of humanization of labor and birth and the role of nurses in the process of humanization of natural childbirth. Conclusion: within the expectations and knowledge of the women were concerned about having a birth with little pain and suffering, without major complications for mother and for the baby. It is evident that the lack of information on women's rights and your body ends up being a factor in convincing that it does not have the natural childbirth as a first choice. With regard to the Program for Humanization of Delivery and Birth and the role of nurses in the humanization of labor, there is need to improve access to coverage and quality of monitoring of prenatal and birth; encourage the importance of breastfeeding, rooming-in and the presence of companion. Descriptors: nursing; parturition; humanizing delivery.